2019
DOI: 10.3390/lubricants8010003
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Graphene Platelets as Dry Lubricant and as Grease Additive for Sliding Contacts and Rolling Bearing Application

Abstract: In recent years, graphene-based lubrication was in the focus of nano- and microtribological studies. While the sliding properties of graphene based dry lubrication were previously investigated on the nano- and micro-scale, few studies can be found in the literature for the application of graphene as an additive to oil and grease in rolling contacts. In order to apply graphene platelets as dry lubricants and as grease additives in machine elements, tests were carried out on a rolling bearing test rig under typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Numerous studies have assessed the ability of 2D materials to improve friction, wear, and service life in rolling element bearings, [137] such as axial [29,[138][139][140] and/or radial bearings [141][142][143][144][145][146] as well as with [29,[141][142][143][144][145][146] and without retainer elements or cages. [138][139][140]147] The availability of fully developed industrial-scale PVD processes for deposition of the MoS 2 coatings resulted in MoS 2 being the most studied material among others.…”
Section: Rolling Bearingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have assessed the ability of 2D materials to improve friction, wear, and service life in rolling element bearings, [137] such as axial [29,[138][139][140] and/or radial bearings [141][142][143][144][145][146] as well as with [29,[141][142][143][144][145][146] and without retainer elements or cages. [138][139][140]147] The availability of fully developed industrial-scale PVD processes for deposition of the MoS 2 coatings resulted in MoS 2 being the most studied material among others.…”
Section: Rolling Bearingsmentioning
confidence: 99%
“…[138][139][140]147] The availability of fully developed industrial-scale PVD processes for deposition of the MoS 2 coatings resulted in MoS 2 being the most studied material among others. [138][139][140][141][142][143][144][145] Yet, some application-oriented studies on WS 2 , [148] graphene, [146] and MXenes [29] have been performed as well. Apart from coatings for the highly loaded primary contacts between rolling elements and the raceways of bearing rings/washers, [29,[138][139][140][141][142][143]146] some studies addressed secondary contacts with lower loads but higher slip and sliding velocities such as the contact between the rolling elements and cage pockets with 2D nanomaterials as inserts or reinforcement phases of composites.…”
Section: Rolling Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [41] have performed wear tests in a four-ball assembly on a polyalphaolefin-2 (PAO-2) oil enriched with multi-layered graphene, measuring a 78%-reduction of the friction coefficient and a beneficial reduction of wear rate. Pape et al [42] have employed 1 wt % of graphene platelets with different thicknesses (2, 6-8, 11-15 nm) as dry lubricants and as additives in greases for rolling contacts operating under reciprocating motion. They have concluded that the excellent wear resistance and friction coefficient reduction are associated to the platelets covering the surface asperities and generating favorable sliding planes, although thickness seemed to not influence the performances.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of mechanical and wetting methods could then ap-pear as possible new paths for van der Waals 2D systems detachment and transfer to other substrates [69]. Our results may also contribute to better understand the response of graphene based coatings in different environments submitted to mechanical constraints as in their use in tribological contacts [70][71][72].…”
Section: Discussion and Modellingmentioning
confidence: 81%